Temporality and writing. Hispanic-Argentine syncronies in the narrative of Felix Bruzzone and Mariana Eva Perez - Mariela Paula Sánchez (Estudios de Teoría Literaria, 2016)
Consideration of Spain in a chronological advance with a closer history or a history of major disagreements depending on circumstances reproduces the indelible mark of conquest and survives a need to justify the mention of Spain or the incorporation of Spanish names in these latitudes to account for that which is being taken into consideration is somewhere different and presents a break point before any possibility of monolithic Hispanic identity. A timeline with strong milestones about imperialism seems to prevent the trial from any other experience of temporality. Now, what happens when a new approach is given from the appropriation which is a significant time shift, accompanied by a spatial gap, and also a distortion of those aspects of Spain that seem to move chronologically flush with the context from which it brings to mind? The detail that will be held in the stories “El orden de todas las cosas” and “Sueño con medusas”, by Bruzzone, and in Diario de una Princesa Montonera, by Mariana Eva Perez, considers two narrative experiences that are disruptively linked to Spain, wrecking with a kind of accompaniment addressed chronologically and indicted, to lead, however, a relationship over time which shows signs of a memory exercise well away from the idea of linear progression and any semblance of continuity.